Vaccination errors reported to the Vaccine Adverse Event Reporting System, (VAERS) United States, 2000–2013. Issue 28 (22nd June 2015) - Hibbs, Beth F.; Moro, Pedro L.; Lewis, Paige; Miller, Elaine R.; Shimabukuro, Tom T.
Abstract Importance Vaccination errors are preventable events. Errors can have impacts including inadequate immunological protection, possible injury, cost, inconvenience, and reduced confidence in the healthcare delivery system. Objectives To describe vaccination error reports submitted to the Vaccine Adverse Event Reporting System (VAERS) and identify opportunities for prevention. Methods We conducted descriptive analyses using data from VAERS, the U.S. spontaneous surveillance system for adverse events following immunization. The VAERS database was searched from 2000 through 2013 for U.S. reports describing vaccination errors and reports were categorized into 11 error groups. We analyzed numbers and types of vaccination error reports, vaccines involved, reporting trends over time, and descriptions of errors for selected reports. Results We identified 20, 585 vaccination error reports documenting 21, 843 errors. Annual reports increased from 10 in 2000 to 4324 in 2013. The most common error group was "Inappropriate Schedule" (5947; 27%); human papillomavirus (quadrivalent) (1516) and rotavirus (880) vaccines were most frequently involved. "Storage and Dispensing" errors (4983; 23%) included mostly expired vaccine administered (2746) and incorrect storage of vaccine (2202). "Wrong Vaccine Administered" errors (3372; 15%) included mix-ups between vaccines with similar antigens such as varicella/herpes zoster (shingles), DTaP/Tdap, and pneumococcal conjugate/polysaccharide. For error reports with an adverse health event (5204; 25% of total), 92% were classified as non-serious. We also identified 936 vaccination error clusters (i.e., same error, multiple patients, in a common setting) involving over 6141 patients. The most common error in clusters was incorrect storage of vaccine (582 clusters and more than 1715 patients). Conclusions Vaccination error reports to VAERS have increased substantially. Contributing factors might include changes in reporting practices, increasing complexity of the immunization schedule, availability of products with similar sounding names or acronyms, and increased attention to storage and temperature lapses. Prevention strategies should be considered.